JavaScript for absolute beginners - McNavage, Terry (Expert's voice in Web development., 2010)
If you are new to both JavaScript and programming, this hands-on book is for you. Rather than staring blankly at gobbledygook, you'll explore JavaScript by entering and running hundreds of code samples in Firebug, a free JavaScript debugger. Then in the last two chapters, you'll leave the safety of Firebug and hand-code an uber cool JavaScript application in your preferred text editor. Written in a friendly, engaging narrative style, this innovative JavaScript tutorial covers the following essentials: Core JavaScript syntax, such as value types, operators, expressions, and statements provided by ECMAScript. Features for manipulating XHTML, CSS, and events provided by DOM. Object-oriented JavaScript, including prototypal and classical inheritance, deep copy, and mixins. Closure, lazy loading, advance conditional loading, chaining, currying, memoization, modules, callbacks, recursion, and other powerful function techniques. Encoding data with JSON or XML. Remote scripting with JSON-P or XMLHttpRequest Drag-and-drop, animated scrollers, skin swappers, and other cool behaviors. Optimizations to ensure your scripts run snappy. Formatting and naming conventions to prevent you from looking like a greenhorn. New ECMAScript 5, DOM 3, and HTML 5 features such as Object.create(), Function.prototype.bind(), strict mode, querySelector(), querySelectorAll(), and getElementsByClassName(). As you can see, due to its fresh approach, this book is by no means watered down. Therefore, over the course of your journey, you will go from JavaScript beginner to wizard, acquiring the skills recruiters desire.